Scleral buckle infections: microbiological spectrum and antimicrobial susceptibility - Chhablani, Jay (Springer, 2013)
BACKGROUND: The purpose of the present study was to evaluate the microbiological spectrum and antimicrobial susceptibility in patients with scleral buckle infection. Medical records of all the patients diagnosed as buckle infection at L. V. Prasad Eye Institute between July 1992 and June 2012 were reviewed in this non-comparative, consecutive, retrospective case series. FINDINGS: A total of 132 eyes of 132 patients underwent buckle explantation for buckle infection during the study period. The incidence of buckle infection at our institute during the study period was 0.2% (31 out of 15,022). A total of 124 isolates were identified from 102 positive cultures. The most common etiological agent isolated was Staphylococcus epidermidis (27/124, 21.77%) followed by Mycobacterium sp. (20/124, 16.13%) and Corynebacterium sp. (13/124, 10.48%). The most common gram negative bacilli identified was Pseudomonas aeruginosa (9/124, 7.26%). The median interval between scleral buckling surgery and onset of symptoms of local infection was 30 days. All eyes underwent buckle explantation and median time interval between primary SB surgery and explantation was 13 months. Recurrent retinal detachment was observed in two cases at 7 and 48 months, respectively, after buckle explantation. Gram positive, gram negative, and acid-fast organisms isolated from 2003 to 2012 were most commonly susceptible to vancomycin (100%), ciprofloxacin (100%), and amikacin (89%). Susceptibility to ciprofloxacin during the same time period was observed in 75% (15/20), 100% (13/13), and 87% (7/8) of gram positive, gram negative, and acid-fast isolates, respectively. CONCLUSION: Scleral buckle infection is relatively rare and has a delayed clinical presentation. It is most commonly caused by gram positive cocci. Based on the current antimicrobial susceptibility, ciprofloxacin can be used as empirical therapy in the management of scleral buckle infections.